2012
DOI: 10.1590/s1678-91992012000400005
|View full text |Cite
|
Sign up to set email alerts
|

A biodistribution study of Hemiscorpius lepturus scorpion venom and available polyclonal antivenom in rats

Abstract: Abstract:The purpose of the present study was to investigate the biodistribution profile of the venom of Hemiscorpius lepturus, the most dangerous scorpion in Iran. Blood and tissue samples were taken at various predetermined intervals during a 400-minute period for the venom and a 360-minute period for the antivenom in rats. The radio-iodination was carried out using the chloramine-T method. The results showed that the descending order of venom uptake was skin, kidneys and intestine, respectively. The descend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…The mortality rate from H. lepturus envenomation is approximately 60 times higher than the other Iranian scorpions [8]. The most severe toxicity has been primarily reported in children [9]. Unlike other scorpions, the venom of H. lepturus is highly cytotoxic which could be the reason for its complicated clinical manifestations in envenomed people [10].…”
Section: Introductionmentioning
confidence: 99%
“…The mortality rate from H. lepturus envenomation is approximately 60 times higher than the other Iranian scorpions [8]. The most severe toxicity has been primarily reported in children [9]. Unlike other scorpions, the venom of H. lepturus is highly cytotoxic which could be the reason for its complicated clinical manifestations in envenomed people [10].…”
Section: Introductionmentioning
confidence: 99%
“…The pharmacokinetics parameters and the biodistribution profile of venom during a 400 - minute period for the venom have already been published. This study was performed using the chloramine-T method [ 10 ]. In the present study, the biodistribution of H.lepturus scorpion venom was investigated by the longest available period of lasting radiolabeled venom.…”
Section: Discussionmentioning
confidence: 99%
“…Commonly there are only a few case reports on direct cardio-toxic effects of scorpion envenomation in human beings [8]. However, previous studies on the envenomation by H. lepturus indicated that there are in vivo arrhythmogenic and negative effects in rabbits [9,10]. A recent study has shown that the venom from H. lepturus has an ability of cytotoxicity through concentrationand time dependent manner.…”
Section: Curcumin Protects Mitochondria and Cardiomyocytes From Oxidamentioning
confidence: 99%